Health Risk Assessment of Hydrogen Sulfide (H₂S) Exposure Among Communities Near a Bioethanol Industry: A Case Study from Mojokerto, Indonesia - Fatmalia, Nabila; Khambali, Khambali; Sulistio, Irwan; Rachmania; Rosyid, Muhammad Agus Ainur; Amin, Muhammad (Jurnal Higiene Sanitasi, 2025)
The community of Gempolkerep village still smells an unpleasant odour indicated by the presence of H₂S gas in the bioethanol plant. Due to the unpleasant and pungent odour, people in Gempolkerep village experience complaints such as sore eyes, sneezing, coughing, sore throat, shortness of breath, and dizziness. This study aims to determine the effect of H₂S gas exposure on subjective complaints of the community around the bioethanol plant. This research is a quantitative research with a cross-sectional design. The population in this study were housewives of Gempolkerep village of 940 people and measurement of H₂S gas levels in ambient air in Gempolkerep village, Mojokerto district. The sample in this study was taken from a portion of the population with a sample size of 273 respondents. The sampling technique used in this study was purposive sampling method. Data analysis using chi-square statistical test. The results showed that the average measurement of hydrogen sulfide gas levels at the first point was 28.3 µg/Nm3 and at the second point was 15 µg/Nm3. The variables of age, length of exposure, and exposure distance have a significant relationship to subjective complaints with a value of (p-value = 0.000), (p-value = 0.008), and (p-value = 0.001) to the subjective complaints of the people of Gempolkerep Village, but there is no influence of medical history on the subjective complaints of the people of Gempolkerep Village in 2024. The conclusion of this study is that H₂S levels do not affect subjective complaints in the people of Gempolkerep Village in 2024. The advice given to the community is that they can plant ylang-ylang trees, which help reduce the level of pollutants in the air. In addition, the community must be able to maintain immunity by adopting a healthy lifestyle, eating nutritious foods, protecting the environment, and conducting regular health checks.